Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT GFC Terpadu - Mutiara Dwinofita Sari; Henny Armaniah (Jurnal Riset dan Inovasi Manajemen, 2025)
The work environment is all conditions or situations in the workplace that affect employees in carrying out their duties and responsibilities. Work discipline is the attitude and behavior of employees that shows compliance with the rules, policies, and procedures that have been set by the company or organization. This study aims to determine the extent to which the work environment and work discipline influence employee performance. This study uses a quantitative method, the sampling technique is to use the saturated method, where this study has 50 respondents, the data collection technique is carried out by observation and questionnaires. The results of the calculation of the t test where the sig value has a partial effect on X1 on Y is 0.000 <0.05 and the calculated t value is 4.597> t table 1.679. So that the work environment has a significant effect on employee performance, then the calculation of the t test where the sig value has a partial effect on X2 on Y, The calculation results on the t sig test are 0.009 <0.05 and the calculated t value is 2.740> t table 1.679. where the sig value has a partial effect on X2 on Y, then the calculation of the f sig test is 0.000 <0.05 and the calculated t value is 39.04> t table 3.20 So, which means H3 is accepted, it can be concluded that the work environment X1 and work discipline X2 simultaneously or together have a significant effect on employee performance.